The Arlington study of healthy aging: a multidisciplinary community cohort study of functional decline with age - Delaney L. Davis; Rajvi Shah; Logan Pixler; Dang M. Mai; Juliana Santos; Camille Chandler; Kendall White; Jennifer Nguyen; Ario S. Moradi; Javed Choudhari; Carrie Arena-Marshall; Chase Johnson; et al. (GeroScience, 2026)

Adopted “mammoths” from Alaska turn out to be a whale's tale - Matthew J. Wooller; Pat Drukenmiller; Gonzalo Oteo‐García; Francesca Di Paolo; Love Dalén; Nick Baker; Nancy Bigelow; Stormy Fields; Sambit Ghosh; Kathryn E. Krasinski; Ben Lamm; Alistair J. Monteath; et al. (Journal of Quaternary Science, 2026)
Radiocarbon‐dated fossils indicate woolly mammoths were extirpated from mainland Beringia around 13 000 years ago. However, environmental DNA in permafrost suggests small “cryptic“ populations survived into the Holocene. Resolving this discrepancy is crucial to understanding the drivers of mammoth extinction. The Adopt‐a‐Mammoth project, launched in 2022, is increasing the number of radiocarbon‐dated mammoth fossils to locate the chronologically youngest specimens. Here, we report results from two “mammoth“ vertebral epiphyseal plates from interior Alaska that produced the youngest radiocarbon ages associated with mammoth specimens (~1900–2700 cal a BP). However, isotopic data indicated that these individuals consumed marine resources, and subsequent ancient DNA analysis revealed the specimens were in fact from a North Pacific Right whale and a Minke whale. Solving the mystery of recent “mammoth” fossils raised new questions. How did the remains of ancient whales become emplaced in sediment so far from the coastline? We briefly consider four scenarios to account for this.

Chlorella SLA-04 growth responses to dark period non-circulating, low light conditions in low and high alkalinity - Jessica D. Wood; Isaac R. Miller; Adrienne D. Arnold; Sridhar Viamajala; Robin Gerlach; Matthew W. Fields (Algal Research, 2025)

Biosecurity investment impacts on highly pathogenic avian influenza control in United States commercial turkey operations - Jada M. Thompson; Kelly Patyk; Victoria Fields; Matthew Branan; Amy Delgado; Kylie Roesler (Preventive Veterinary Medicine, 2025)

Which Plant Traits Increase Soil Carbon Sequestration? Empirical Evidence From a Long‐Term Poplar Genetic Diversity Trial - John L. Field; Brandon P. Sloan; Matthew E. Craig; Parker Calloway; Sarah L. Ottinger; Thomas Mead; Rose Z. Abramoff; Mirko Pavicic Venegas; Hari B. Chhetri; Kathy Haiby; Udaya C. Kalluri; Wellington Muchero; et al. (Global Change Biology, 2025)
Plants play a key role in mediating soil response to global change, and breeding or engineering crops to increase soil organic carbon (SOC) storage is a potential route to land‐based carbon dioxide removal in agricultural systems. However, due to limited observational datasets plus shifting paradigms of SOC stabilization, it is unclear which plant traits are most important for enhancing different types of soil organic matter. Existing long‐term common gardens of genetically diverse plant populations may provide an opportunity to evaluate biological controls on SOC, separate from environmental or management variability. Here we report on soil and root chemical data collected for 24 genotypes within a 13‐year‐old common garden in northwestern Oregon planted with a large natural variant population of Populus trichocarpa . Fractionating surface soil (0–15 cm) revealed substantial variation in stocks of mineral‐associated organic matter (MAOM; 18–67 t C/ha) and particulate organic matter (POM; 2–22 t C/ha). Tree genotype explained 24% and 26% of the MAOM and POM stock variability, respectively, after controlling for background variability. We found minimal association between SOC concentration and either aboveground tree productivity or root biomass recalcitrance (C/N ratios and lignin content). In contrast, root elemental content appeared influential for MAOM‐C concentration, which showed a strong positive association with root aluminum (Al) and a strong negative association with root boron (B) and magnesium (Mg). Furthermore, root concentrations of these elements were highly heritable (57%–78%) and not simply a reflection of background variation in soil elemental concentrations. We estimate that surface SOC stocks under these 24 genotypes have diverged at rates of up to 1.2–4.3 t C/ha/year. These results suggest that long‐term genetic diversity trials have value for elucidating biological controls on soil organic matter dynamics, and that traits associated with root elemental content may be a useful target for enhancing biosequestration.

Mapping the pangenome of sulfate reducing bacteria: core genes, plasticity, and novel functions in Desulfovibrio spp. - Shailabh Rauniyar; Dipayan Samanta; Payal Thakur; Priya Saxena; Ram N. Singh; Adelme Bazin; Alain Bomgni; Ernest Fotseu; Gnimpieba Z. Etienne; Venkata Gadhamshetty; Brent M. Peyton; Matthew Fields; et al. (World Journal of Microbiology and Biotechnology, 2025)

Springtime upwelling conditions influence microbial communities and dissolved thiamin compounds in the California Current Ecosystem - Kelly C. Shannon; Gillian St. John; Robin Gould; Christopher Hartzell; Hailey Matthews; Elizabeth J. Brennan; Luis M. Bolaños; Steven T. Lindley; John C. Field; Nate Mantua; Rachel Johnson; Carson Jeffres; et al. (Limnology and Oceanography, 2025)
Understanding dissolved concentrations of the essential coenzyme thiamin (vitamin B 1 ) can provide insights into the biological controls on highly productive upwelling systems such as the California Current Ecosystem. To connect thiamin availability with microbial communities in the California Current Ecosystem, we measured concentrations of dissolved thiamin and its biochemically related moieties (thiamin congeners) and 16S rRNA gene‐based microbial communities during the spring. We found that strong upwelling caused a depletion of dissolved thiamin precursor compounds and abiotic degradation products relative to periods of weak upwelling. Specific microbial taxa, including species of SAR11 ecotypes, Candidatus Nitrosopumilus, and SUP05 cluster, were also significantly enriched with strong upwelling. Our data provide evidence that alterations to microbial communities in the mixed layer that occur as a result of upwelling could constrain the availability of dissolved thiamin and its chemical congeners in the California Current Ecosystem.

One size does not fit all: Intra– and interspecific variation of den site use in two marsupial glider species in fragmented forest - Christopher M. McLean; Jed Field; Samuel A.R. Hayley; Matthew Hingee; Chad T. Beranek (Forest Ecology and Management, 2025)

Stereo-video landers can rapidly assess marine fish diversity and community assemblages - Kinsey E. Matthews; Ryan T. Fields; Kathleen P. Cieri; Jacklyn L. Mohay; Mary G. Gleason; Richard M. Starr (Frontiers in Marine Science, 2024)
Climate change and anthropogenic stressors affect the distribution, abundance, and diversity of fish communities across the world. To understand rapidly changing biotic communities, resource managers need a method to quickly and efficiently document temporal and spatial changes in community assemblages across various spatial scales. In this study, we describe the use of new video lander tools to survey fish communities in rocky marine habitats on the continental shelf and slope in California, USA. We evaluate how fish diversity metrics determined by video surveys vary among geographically distinct areas. Our results demonstrate that species diversity, evenness, and richness vary spatially across the coast. Furthermore, community assemblages differ at both broad and fine spatial scales because of differences among habitats. Length frequencies and densities of species in this study were similar to those reported in previous studies. As community assemblages and biodiversity metrics shift in response to changing stressors, it is increasingly important to develop tools and methodologies to detect and rapidly monitor these changes.

PlantACT! – how to tackle the climate crisis - Heribert Hirt; Salim Al-Babili; Marilia Almeida-Trapp; Antoine Martin; Manuel Aranda; Dorothea Bartels; Malcolm Bennett; Ikram Blilou; Damian Boer; Alix Boulouis; Chris Bowler; Sophie Brunel-Muguet; et al. (Trends in Plant Science, 2023)

Prevalence of neonicotinoid insecticides in paired private-well tap water and human urine samples in a region of intense agriculture overlying vulnerable aquifers in eastern Iowa - Darrin A. Thompson; Dana W. Kolpin; Michelle L. Hladik; Hans-Joachim Lehmler; Shannon M. Meppelink; Matthew C. Poch; John D. Vargo; Victor A. Soupene; Nafis Md Irfan; Morgan Robinson; Kurunthachalam Kannan; Laura E. Beane Freeman; et al. (Chemosphere, 2023)

A possible role for river restoration enhancing biodiversity through interaction with wildfire - Brittany E. Pugh; Megan Colley; Stephen J. Dugdale; Patrick Edwards; Rebecca Flitcroft; Andrés Holz; Matthew Johnson; Michela Mariani; Mickey Means‐Brous; Kate Meyer; Kevan B. Moffett; Lisa Renan; et al. (Global Ecology and Biogeography, 2022)
Background Historically, wildfire regimes produced important landscape‐scale disturbances in many regions globally. The “pyrodiversity begets biodiversity” hypothesis suggests that wildfires that generate temporally and spatially heterogeneous mosaics of wildfire severity and post‐burn recovery enhance biodiversity at landscape scales. However, river management has often led to channel incision that disconnects rivers from their floodplains, desiccating floodplain habitats and depleting groundwater. In conjunction with predicted increases in frequency, intensity and extent of wildfires under climate change, this increases the likelihood of deep, uniform burns that reduce biodiversity. Predicted synergy of river restoration and biodiversity increase Recent focus on floodplain re‐wetting and restoration of successional floodplain habitat mosaics, developed for river management and flood prevention, could reduce wildfire intensity in restored floodplains and make the burns less uniform, increasing climate‐change resilience; an important synergy. According to theory, this would also enhance biodiversity. However, this possibility is yet to be tested empirically. We suggest potential research avenues. Illustration and future directions We illustrate the interaction between wildfire and river restoration using a restoration project in Oregon, USA. A project to reconnect the South Fork McKenzie River and its floodplain suffered a major burn (“Holiday Farm” wildfire, 2020), offering a rare opportunity to study the interaction between this type of river restoration and wildfire; specifically, the predicted increases in pyrodiversity and biodiversity. Given the importance of river and wetland ecosystems for biodiversity globally, a research priority should be to increase our understanding of potential mechanisms for a “triple win” of flood reduction, wildfire alleviation and biodiversity promotion.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Estimated life-history traits and movements of the Caribbean reef shark (Carcharhinus perezi) in The Bahamas based on tag-recapture data - Brendan S. Talwar; Darcy Bradley; Christopher Berry; Mark E. Bond; Ian A. Bouyoucos; Annabelle M. L. Brooks; Candace Y. A. Fields; Austin J. Gallagher; Tristan L. Guttridge; Annie E. Guttridge; Neil Hammerschlag; Ian Hamilton; et al. (Marine Biology, 2022)

Mercury exposure of tidal marsh songbirds in the northeastern United States and its association with nest survival - Katharine J. Ruskin; Garth Herring; Collin A. Eagles-Smith; Alyssa B. Eiklor; Chris S. Elphick; Matthew A. Etterson; Christopher R. Field; Rebecca A. Longenecker; Adrienne I. Kovach; W. Gregory Shriver; Jennifer Walsh; Brian J. Olsen (Ecotoxicology, 2022)

Bulk phase resource ratio alters carbon steel corrosion rates and endogenously produced extracellular electron transfer mediators in a sulfate-reducing biofilm - Gregory P. Krantz; Kilean Lucas; Erica L.- Wunderlich; Linh T. Hoang; Recep Avci; Gary Siuzdak; Matthew W. Fields (Biofouling, 2019)

Microbial community changes during a toxic cyanobacterial bloom in an alkaline Hungarian lake - Tisza A. S. Bell; Emel Sen-Kilic; Tamás Felföldi; Gabor Vasas; Matthew W. Fields; Brent M. Peyton (Antonie van Leeuwenhoek, 2018)

Genetic modifiers of radon-induced lung cancer risk: a genome-wide interaction study in former uranium miners - Albert Rosenberger; Rayjean J. Hung; David C. Christiani; Neil E. Caporaso; Geoffrey Liu; Stig E. Bojesen; Loic Le Marchand; Ch. A. Haiman; Demetrios Albanes; Melinda C. Aldrich; Adonina Tardon; G. Fernández-Tardón; et al. (International Archives of Occupational and Environmental Health, 2018)

Energy conserving thermoregulatory patterns and lower disease severity in a bat resistant to the impacts of white-nose syndrome - Marianne S. Moore; Kenneth A. Field; Melissa J. Behr; Gregory G. Turner; Morgan E. Furze; Daniel W. F. Stern; Paul R. Allegra; Sarah A. Bouboulis; Chelsey D. Musante; Megan E. Vodzak; Matthew E. Biron; Melissa B. Meierhofer; et al. (Journal of Comparative Physiology B, 2018)

Training in the Conduct of Population-Based Multi-Site and Multi-Disciplinary Studies: the Cancer Research Network’s Scholars Program - Diana S. M. Buist; Terry S. Field; Matthew P. Banegas; Heather A. Clancy; V. Paul Doria-Rose; Mara M. Epstein; Robert T. Greenlee; Sarah McDonald; Hazel B. Nichols; Pamala A. Pawloski; Lawrence H. Kushi (Journal of Cancer Education, 2017)

Seasonal fecundity is not related to geographic position across a species’ global range despite a central peak in abundance - Katharine J. Ruskin; Matthew A. Etterson; Thomas P. Hodgman; Alyssa C. Borowske; Jonathan B. Cohen; Chris S. Elphick; Christopher R. Field; Rebecca A. Kern; Erin King; Alison R. Kocek; Adrienne I. Kovach; Kathleen M. O’Brien; et al. (Oecologia, 2017)

The Effects of Histone Deacetylase Inhibitors on Glioblastoma-Derived Stem Cells - Angel A. Alvarez; Melvin Field; Sergey Bushnev; Matthew S. Longo; Kiminobu Sugaya (Journal of Molecular Neuroscience, 2015)

Opportunities for Lean Stability Strategies - Stephen T. Colgan; Robert J. Timpano; Matthew Roberts; Roger Weaver; Kevin Ryan; Kevin W. Fields; Garry Scrivens (Journal of Pharmaceutical Innovation, 2014)

Use of sodium bicarbonate to stimulate triacylglycerol accumulation in the chlorophyte Scenedesmus sp. and the diatom Phaeodactylum tricornutum - Robert D. Gardner; Keith E. Cooksey; Florence Mus; Richard Macur; Karen Moll; Everett Eustance; Ross P. Carlson; Robin Gerlach; Matthew W. Fields; Brent M. Peyton (Journal of Applied Phycology, 2012)

Evaluation and remediation of bulk soap dispensers for biofilm - Lindsey A. Lorenz; Bradley D. Ramsay; Darla M. Goeres; Matthew W. Fields; Carrie A. Zapka; David R. Macinga (Biofouling, 2012)

The volatile content of hypabyssal kimberlite magmas: some constraints from experiments on natural rock compositions - Richard A. Brooker; R. Stephen J. Sparks; Janine L. Kavanagh; Matthew Field (Bulletin of Volcanology, 2011)

Emplacement temperatures of pyroclastic and volcaniclastic deposits in kimberlite pipes in southern Africa - Giovanni Fontana; Conall Mac Niocaill; Richard J. Brown; R. Stephen J. Sparks; Matthew Field (Bulletin of Volcanology, 2011)

Growth of bultfonteinite and hydrogarnet in metasomatized basalt xenoliths in the B/K9 kimberlite, Damtshaa, Botswana: insights into hydrothermal metamorphism in kimberlite pipes - Ben Buse; John C. Schumacher; R. Stephen J. Sparks; Matthew Field (Contributions to Mineralogy and Petrology, 2010)

Hydrogen peroxide‐induced oxidative stress responses in Desulfovibrio vulgaris Hildenborough - Aifen Zhou; Zhili He; Alyssa M. Redding‐Johanson; Aindrila Mukhopadhyay; Christopher L. Hemme; Marcin P. Joachimiak; Feng Luo; Ye Deng; Kelly S. Bender; Qiang He; Jay D. Keasling; David A. Stahl; et al. (Environmental Microbiology, 2010)
Summary To understand how sulphate‐reducing bacteria respond to oxidative stresses, the responses of Desulfovibrio vulgaris Hildenborough to H 2 O 2 ‐induced stresses were investigated with transcriptomic, proteomic and genetic approaches. H 2 O 2 and induced chemical species (e.g. polysulfide, ROS) and redox potential shift increased the expressions of the genes involved in detoxification, thioredoxin‐dependent reduction system, protein and DNA repair, and decreased those involved in sulfate reduction, lactate oxidation and protein synthesis. A gene coexpression network analysis revealed complicated network interactions among differentially expressed genes, and suggested possible importance of several hypothetical genes in H 2 O 2 stress. Also, most of the genes in PerR and Fur regulons were highly induced, and the abundance of a Fur regulon protein increased. Mutant analysis suggested that PerR and Fur are functionally overlapped in response to stresses induced by H 2 O 2 and reaction products, and the upregulation of thioredoxin‐dependent reduction genes was independent of PerR or Fur. It appears that induction of those stress response genes could contribute to the increased resistance of deletion mutants to H 2 O 2 ‐induced stresses. In addition, a conceptual cellular model of D. vulgaris responses to H 2 O 2 stress was constructed to illustrate that this bacterium may employ a complicated molecular mechanism to defend against the H 2 O 2 ‐induced stresses.

Biofilm formation in Desulfovibrio vulgaris Hildenborough is dependent upon protein filaments - Melinda E. Clark; Richard E. Edelmann; Matt L. Duley; Judy D. Wall; Matthew W. Fields (Environmental Microbiology, 2007)
Summary Desulfovibrio vulgaris Hildenborough is a Gram‐negative sulfate‐reducing bacterium (SRB), and the physiology of SRBs can impact many anaerobic environments including radionuclide waste sites, oil reservoirs and metal pipelines. In an attempt to understand D. vulgaris as a population that can adhere to surfaces, D. vulgaris cultures were grown in a defined medium and analysed for carbohydrate production, motility and biofilm formation. Desulfovibrio vulgaris wild‐type cells had increasing amounts of carbohydrate into stationary phase and approximately half of the carbohydrate remained internal. In comparison, a mutant that lacked the 200 kb megaplasmid, strain ΔMP, produced less carbohydrate and the majority of carbohydrate remained internal of the cell proper. To assess the possibility of carbohydrate re‐allocation, biofilm formation was investigated. Wild‐type cells produced approximately threefold more biofilm on glass slides compared with ΔMP; however, wild‐type biofilm did not contain significant levels of exopolysaccharide. In addition, stains specific for extracellular carbohydrate did not reveal polysaccharide material within the biofilm. Desulfovibrio vulgaris wild‐type biofilms contained long filaments as observed with scanning electron microscopy (SEM), and the biofilm‐deficient ΔMP strain was also deficient in motility. Biofilms grown directly on silica oxide transmission electron microscopy (TEM) grids did not contain significant levels of an exopolysaccharide matrix when viewed with TEM and SEM, and samples stained with ammonium molybdate also showed long filaments that resembled flagella. Biofilms subjected to protease treatments were degraded, and different proteases that were added at the time of inoculation inhibited biofilm formation. The data indicated that D. vulgaris did not produce an extensive exopolysaccharide matrix, used protein filaments to form biofilm between cells and silica oxide surfaces, and the filaments appeared to be flagella. It is likely that D. vulgaris used flagella for more than a means of locomotion to a surface, but also used flagella, or modified flagella, to establish and/or maintain biofilm structure.

Transcriptional Regulation of β-Glucanase Activity in the Ruminal Bacterium, Prevotella bryantii B14 - Matthew W. Fields; James B. Russell (Current Microbiology, 2005)

Molecular diversity and characterization of nitrite reductase gene fragments ( nir K and nir S) from nitrate‐ and uranium‐contaminated groundwater - Tingfen Yan; Matthew W. Fields; Liyou Wu; Yuangang Zu; James M. Tiedje; Jizhong Zhou (Environmental Microbiology, 2003)
Summary Nitrate‐contaminated groundwater samples were analysed for nir K and nir S gene diversity. The samples differed with respect to nitrate, uranium, heavy metals, organic carbon content, pH and dissolved oxygen levels. A total of 958 nir K and 1162 nir S clones were screened by restriction fragment length polymorphism (RFLP) analysis: 48 and 143 distinct nir K and nir S clones, respectively, were obtained. A single dominant nir K restriction pattern was observed for all six samples and was 83% identical to the Hyphomicrobium zavarzinii nir K gene. A dominant nir S pattern was observed for four of the samples, including the background sample, and was 95% identical to the nir S of Alcaligenes faecalis. Diversity indices for nir K and nir S sequences were not related to any single geochemical characteristic, but results suggested that the diversity of nir K genes was inversely proportional to the diversity of nir S. Principal component analysis (PCA) of the sites based on geochemistry grouped the samples by low, moderate and high nitrate but PCA of the unique operational taxonomic units (OTUs) distributions grouped the samples differently. Many of the sequences were not closely related to previously observed genes and some phylogenetically related sequences were obtained from similar samples. The results indicated that the contaminated groundwater contained novel nir K and nir S sequences, functional diversity of both genes changed in relation to the contaminant gradient, but the nir K and nir S functional diversity was affected differently.

Cues paired with a low dose of alcohol acquire conditioned incentive properties in social drinkers - Matthew Field; Theodora Duka (Psychopharmacology, 2002)

A Prevotella ruminicola B 1 4 Operon Encoding Extracellular Polysaccharide Hydrolases - Richard G. Gardner; James E. Wells; Matthew W. Fields; David B. Wilson (Current Microbiology, 1997)